Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Siswa Pada Materi Pokok Pewasat Sederhana Di Kelas VIII SMP Negeri 14 Medan - Warsidah; Mariana Surbakti (Jurnal Visi Eksakta, 2023)
Ale-ale shells are popular shellfish in the Ketapang coastal area. The local community uses the shellfish a lot as food processing, one of which is in the form of fermented products. In the fermentation process, the nutritional content of course will be different from fresh ale-ale because it has gone through the preservation process. In this study, several work procedures were carried out for proximate testing including measuring pH, determining water content, ash content, protein content, fat content and carbohydrate content. The proximate content in fermented products is different and tends to decrease, such as protein content, fat content, carbohydrates. This is due to the difference in preparations between fresh ale-ale and fermented ale-ale products. The purpose of testing proximate levels is to determine the difference in proximate content between fresh ale and ale ale that is processed by fermentation.